Myths and realities of digital reference services: perspectives of libraries from developing countries - Abu Bakar, Ahmad Bakeri (Emerald Group Publishing Limited, 2012)
Purpose – The purpose of this paper is to determine whether differences exist between public and private universities' web sites in terms of visibility and accessibility of the web sites.